BINDING OF CROWN ETHER Bz9C3, Bz12C4 AND Bz15C5 TO CATIONS BASED ON SEMIEMPIRICAL ORBITAL MOLECULAR CALCULATIONS - , Harno Dwi Pranowo, Tutik Dwi Wahyuningsih ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
Selectivity of crown ether to bind a cation was analyzed based on computational chemistry calculations using MNDO/d semi empirical method. The effect of substituents of -COOH, -Br, -COOC2H5, -CHO, -CH=CHCO2H, -CH=CHCO2C2H5 and -CH(OH)CH3 on bz9C3, bz12C4, and bz15C5, and interaction between these crown ethers with metal cations was evaluated using computational chemistry calculations. The first step is structure optimization of crown ether followed by optimization of crown ether-metals cation complexes Mn+.[Crown ether], where M is Li+, and Na+. Interactions of the crown ether and cation were discussed in term of the structure parameter of crown ether, atomic charges and energy interaction of the crown ether-metals cation. If the diameter of cation is higher than cavity of crown ether, the complexes of crown ether-cation were modeled as crown ether:cation (1:1), crown ether:cation (2:1) and crown ether:cation:H2O complexes. While the cation bind in the cavity of crown ether, the complexes of crown ether:cation was modeled as crown ether:cation (1:1), crown ether:cation:H2O and crown ether:cation:2H2O complexes. Electron donating groups increase the capability of crown ether to bind cation by means of induction effect, while electron withdrawing groups reduce the ability of crown ether to bind cation. Any substituent on the benzene in crown ether which can be make the symmetrical form of the crown ether-metals cation complexes will increase the selectivity of the crown ether to bind the cation. Selectivity of the crown ether to bind cation also depends on the compatibility of the diameter of cation and cavity of crown ether.